Comportamiento epidemiológico del dengue en Loreto del 2018 hasta el 2021 - Dávila Guerra, Derwin Soler (2022)
The dengue virus represents a constant problem for public health in all the countries that suffer from this disease, so its importance lies in knowing as much as possible about its epidemiological behavior, since this information will be used to implement preventive measures. prevention and control to strengthen health services in our region. The objective of this research was to describe the epidemiological behavior of dengue in Loreto from 2018 to 2021. The research design was descriptive, retrospective, cross-sectional. The study population was 1,423 patients in 2018, in 2019 3,107 patients were involved, in 2020 the patients were a total of 12,895 and in 2021 7,345 patients were registered. The information collection process was through a database provided and authorized by DIRESA-Loreto. The results show that, within the years of study, the largest number of dengue cases were reported in 2020 (52.3%) and 2021 (29.4%), where the most affected population was the female sex with a percentage of 53.38 %, and the most affected age groups were children from 1 to 12 years old (28.0%) and adults from 31 to 59 years old (30.0%). The most affected provinces in the Loreto region were Maynas with 54.8%, Alto Amazonas 30.7%, Loreto 5.7% and finally Ucayali 4.0%. Similarly, the most affected districts in the region were Yurimaguas 27.8%, San Juan Bautista 22.6%, Iquitos 14.4%, Punchana 8.4%, Nauta 4.3% and finally Belén with 4.1%.